MEMAHAMI FENOMENA LEMAHNYA KETERAMPILAN BERBAHASA MAHASISWA STKIP WEETEBULA - Silvester Nusa; Wilhelmus Yape Kii (SekolahTinggi Keguruan dan Ilmu Pendidikan (STKIP), 2017)
The purpose of this study was to asses some factors that influence the low-ability of speakingwriting skills of bahasa for STKIP (Higher College for Teacher Candidate) students. The phenomenon of the low-ability of speaking-writing skills can be identified through several mistakes such as incorrect spelling, incorrect diction, incorrect sentence structure, incorrect coherence etc. A good-ability of speaking-writing skills of bahasa required for university students, particularly for teacher candidate.The subject of this study was 11 STKIP students from Bahasa Indonesia Study Program and 6 language (bahasa) teachers from SMA (Senior High School) and SMK (Vocational High School) at Sumba Barat DayaDistrict. This study was using Qualitative Method and data was collected through semi-structured interview. In addition, Miles and Huberman Model that consists of data reduction, data presentation and conclusion, was using for data analysis purposed. The results of this study showed thatthe low-ability of speaking-writing skills of bahasa for STKIP students was caused by physiological factors (attitude, interest, and motivation) and non-physiological factors (local/first language, surrounding environments, and bahasa as a second language on school system at this island)Keywords: mistakes on speaking-writing skills, physiological factors, non-physiological factors